Evaluation of Heavy Metals Concentration in Milk Products by using Atomic Absorption Spectroscopy - Nurul Auni Zainal Abidin; Nur Sofiah Abu Kassim Kassim; Sheikh Ahmad Izzadin; Sheikh Mohd Ghazali; Noor Hidayah Pungot; Siti Sufiana Kamni (EKSAKTA: Journal of Sciences and Data Analysis, 2021)
Milk products are essential food in the human diet because it contains many essential trace minerals such as calcium, magnesium, copper, zinc, sodium, potassium and phosphorous. The utilization of, milk is increasing at a large scale throughout the world. It is essential to maintain the good quality of milk during production and manufacturing because the presence of toxic metals in the milk becomes the cause of health disturbance in human life. Therefore, the present investigation was carried out to determine concentrations of lead, nickel, iron, copper, and chromium in powdered milk and fresh milk products by Atomic Absorption Spectroscopy. Different milk samples of products (two fresh milks and two powdered milks) were purchased from the local market. For the decomposition of the organic substances in milk samples, wet digestion was used with a mixture of nitric acid and sulfuric acid in volume proportions 1:3 (v/v). The analytical curve for all metals covered the linear range from 0.5 to 4.0 ppm with correlation coefficients higher than 0.9994. The limit of detection (LOD) for Pb, Ni, Fe, Cu, and Cr were found to be 0.25, 0.023, 0.012, 0.0067, and 0.073 ppm, respectively. While the limit of quantification (LOQ) in the range of 0.02 to 0.76 ppm. Of all the metals determined, Pb, Ni, and Fe were the most abundant with concentrations between 1.233 and 1.677 ppm while Cr was not detected in all the samples. The results showed that fresh milk samples have a higher concentration of heavy metals compared to powdered milk samples.